2021
DOI: 10.26444/aaem/131555
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy of lay people and health professionals perception of physical activity is a challenge for activity education and promotion within primary health care – a qualitative study

Abstract: of lay people and health professionals perception of physical activity is a challenge for activity education and promotion within primary health care -a qualitative study. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…For instance, in a study on the dichotomy of lay people and health professionals' perception of physical activity as a barrier for activity education and promotion in primary health care, Cianciara and colleagues found that lay people appreciated physical activity as an important and controllable health determinant with psychosocial benefits. This contrasted with health professionals who associated physical activity with disease risk reduction [33]. The same study reports that lay persons perceptions of barriers to physical activity were associated with what the authors named "real-life factors" such as having sportswear, access to sport facilities, and job opportunities [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a study on the dichotomy of lay people and health professionals' perception of physical activity as a barrier for activity education and promotion in primary health care, Cianciara and colleagues found that lay people appreciated physical activity as an important and controllable health determinant with psychosocial benefits. This contrasted with health professionals who associated physical activity with disease risk reduction [33]. The same study reports that lay persons perceptions of barriers to physical activity were associated with what the authors named "real-life factors" such as having sportswear, access to sport facilities, and job opportunities [33].…”
Section: Discussionmentioning
confidence: 99%
“…This contrasted with health professionals who associated physical activity with disease risk reduction [33]. The same study reports that lay persons perceptions of barriers to physical activity were associated with what the authors named "real-life factors" such as having sportswear, access to sport facilities, and job opportunities [33].…”
Section: Discussionmentioning
confidence: 99%